Uterine cellular changes during mammalian pregnancy and the evolution of placentation. Issue 6 (11th September 2021) - Dudley, Jessica S; Murphy, Christopher R; Thompson, Michael B; McAllan, Bronwyn M
Abstract: There are many different forms of nutrient provision in viviparous (live-bearing) species. The formation of a placenta is one method where the placenta functions to transfer nutrients from mother to fetus (placentotrophy), to transfer waste from the fetus to the mother, and to perform respiratory gas exchange. Despite having the same overarching function, there are different types of placentation within placentotrophic vertebrates, and many morphological changes occur in the uterus during pregnancy to facilitate formation of the placenta. These changes are regulated in complex ways but are controlled by similar hormonal mechanisms across species. This review describes current knowledge of the morphological and molecular changes to the uterine epithelium preceding implantation among mammals. Our aim is to identify the commonalities and constraints of these cellular changes to understand the evolution of placentation in mammals and to propose directions for future research. We compare and discuss the complex modifications to the ultrastructure of uterine epithelial cells (UEC) and show that there are similarities in the changes to the cytoskeleton and gross morphology of the UEC, especially of the apical and lateral plasma membrane of the cells during the formation of a placenta in all eutherians and marsupials studied to date. We conclude that further research is needed to understand the evolution of placentation among viviparous mammals, particularly concerning the level of placental invasiveness, hormonal control, and genetic underpinnings of pregnancy in marsupial taxa. Abstract : There are many complex modifications to the ultrastructure of uterine epithelial cells during pregnancy with similarities in the changes to their gross morphology during the formation of a placenta in eutherians and marsupials studied to date. Graphical Abstract: